O projekcie kontekstowego rozumienia języka pisanego na potrzeby systemu automatycznej poprawy błędów dla języka polskiego - Witkowska, Katarzyna (Papers in Linguistics, 2021)
The project of contextual understanding of the written language for the purpose of an error correction system designed for the Polish language